Gorbacsov és CeauÈ™escu utolsó találkozója - Sztikalin, Alexandr (Acta Scientiarum Socialium, 2016)
The last meeting of Gorbachev and CeauÈ™escu. The Romanian record on M. Gorbachev’s meeting with N. CeauÈ™escu on December 4th, 1989 is first published for Hungarian readers in the present article. This event was given great importance and topicality by the regime changes in Central- and Eastern-European countries. By this time even in Romania, the last country of Stalin-type dictatorship, social tensions had become tangible, and only a few weeks were left until the Conducator’s execution. From the content of the conversation we can see that CeauÈ™escu was left no legs to stand on, but at the same time he clung onto power with tooth and nail, but he could not rely on any support from Gorbachev. As it becomes clear from their conversation, the Soviet and Romanian leaders had very different views on the international situation, the question of reforms and structural reorganisations, future perspectives, and they intended to give different answers to the challenges they were faced with.